Informational dimension of HIV/AIDs problem inside Internally Displaced Persons community of Nigeria - Verlumun Celestine Gever; Gabriel Alhassan Ottah (Cхід, 2020)
This study examined information seeking behaviour of Internally Displaced Persons (IDPs) in Benue State with a view to understanding how to best communicate HIV/AIDS services to them as well as promote policies that could help combat child poverty. A total of 384 IDPs were sampled from four IDP centres in Benue State. The indices that were measured in this study included sources of information, motivation for information seeking, information seeking behaviour, attention to source credibility and knowledge of HIV/AIDs. To measure sources of information, the respondents were requested to provide the sources through which they receive information and also indicate the motivation for doing so. The information seeking behaviour of the respondents was accessed using by classifying the information seeking behaviour of the sample into low information seeking behaviour and high information seeking behaviour. The indices for high and low information seeking behaviour were presented to the respondents who indicated their information seeking behaviour. Attention to source credibility was measured using a dichotomous response format of ‘yes’ and ‘no’ which was used to assess source credibility. The two dimensions of that were used are trustworthiness and expertise. Therefore, the researchers asked the respondents to ascertain if they pay attention to source trustworthiness and expertise in their information seeking behaviour. Concerning the knowledge of HIV/AIDS status, the respondents were asked to report if they were aware of their HIV/AIDs status or not. They were asked to indicate their actual status because of the sensitivity of the matter. In the analysis of data for this study, the researcher used both descriptive and inferential statistics. Among the descriptive statistics, simple percentages were used while among the inferential statistics, chi-square test of independence was used. The hypotheses were tested at 0.05 level of significance. The result showed that most of the IDPs get information from family and friends. Information seeking behaviour was found to have significantly associated with sources of information and motivation for seeking information. Also, perceived HIV/Aids information need was associated with information seeking behaviour. HIV/Aids status was also associated with information seeking behaviour. Finally, significant relationship exists between information seeking behaviour of consciousness of source credibility. The implications of these results on HIV/AIDs communication policies are also explored.